# Solve for x $\sin^{-1}\frac{2\alpha}{1+\alpha^2}+ \sin^{-1}\frac{2\beta}{1+\beta^2}=2\tan^{-1}x.$

## 1 Answer

Toolbox:
• $$sin2A= \large\frac{2tanA}{1=tan^2A}$$
• $$tan^{-1}x+tan^{-1}y=tan^{-1}\large\frac{x+y}{1-xy}$$
put $$\alpha = tanA \: and \: \beta = tanB$$
$$\Rightarrow\: A=tan^{-1}\alpha \; \: B=tan^{-1}\beta$$
$$\large\frac{2\alpha}{1+\alpha^2}=\large\frac{2tanA}{1+tan^2A}=sin2A$$
$$\large\frac{2\beta}{1+\beta^2}=\large\frac{2tanB}{1+tan^2B}=sin2B$$

Substituting in L.H.S. we get
$$sin^{-1} \large\frac{2\alpha}{1+\alpha^2}+sin^{-1}\large\frac{2\beta}{1+\beta^2}$$
$$sin^{-1} sin2A+sin^{-1}\: sin2B$$
$$=2A+2B=2(A+B)=2 \bigg[ tan^{-1}\alpha+tan^{-1}\beta \bigg]$$

Substituting L.H.S. in the given equation , we get
$$\Rightarrow 2(tan^{-1}\alpha + tan^{-1}\beta) =2 tan^{-1}x$$
$$\Rightarrow tan^{-1}\alpha + tan^{-1}\beta = tan^{-1}x$$
By taking $$\alpha$$ in the place of x and $$\beta$$ in the place of y in the above forfula of $$tan^{-1}x+tan^{-1}y$$we get
$$\Rightarrow\: tan^{-1}\alpha + tan^{-1}\beta= tan^{-1}\large\frac{\alpha+\beta}{1-\alpha\beta}=tan^{-1}x$$
or $$\Rightarrow\: x=\large\frac{\alpha+\beta}{1-\alpha\beta}$$

answered Feb 19, 2013
edited Mar 19, 2013

1 answer

1 answer

1 answer

1 answer

1 answer

1 answer

1 answer